Makroekologija: Analiza biodiverzitetnih podatkov - Janžekovič , Franc (2023)
Macroecology: Analysis of Biodiversity Data. Macroecology, Biodiversity Data Analysis is a university textbook aimed at acquiring knowledge in the field of biotic diversity sciences. The content includes all areas of biodiversity encountered by the modern biological, ecological and nature conservation profession. The methodology of biodiversity research is presented, which follows the concept of dividing biodiversity into three aspects: species, functional and phylogenetic diversity. In the case of species and functional diversity, richness and variety evaluations and methods of species richness assessment are presented. The spatial concept of diversity with alpha, beta, gamma and zeta diversity estimators is presented. Phylogenetic diversity comprises the contents of phylogenetic reconstructions based on morphological and genetic characters. Estimators of phylogenetic diversity, taxonomic diversity and phylogenetic signal analysis are presented. The content of the analysis of ecological communities includes the Q and R approach of evaluation and calculation of indicator with which we investigate the relationships between communities. Biodiversity patterns and processes in space and time are discussed: the relationship between diversity and area size, the relationship between diversity and latitude, the relationship between diversity and altitude, and the response of diversity along ecological gradients. The methodology of morphometric analyses includes a traditional approach and an approach with geometric morphometrics for the purpose of taxonomic analysis and analysing phenotypic plasticity. General methodological content, which extends to the field of sampling and monitoring, as well as content on regressions and statistical inference, important for the study of biodiversity, are presented.
Keywords: macroecology; biodiversity; phylogenetic diversity; species diversity; functional diversity